Developing and validating a nomogram for predicting endoscopic hemostasis failure in cirrhotic patients with esophageal variceal bleeding - Guo, Yali; Ouyang, Hui; Su, Jingling; Zhong, Mingrong; Huang, Wenzhong; Huang, Mingcheng; Xie, Chenxi (Frontiers in Medicine, 2025)
Background and aimsThis study aimed to create and validate a model to predict the failure of endoscopic hemostasis in Chinese cirrhosis patients with acute esophagogastric variceal bleeding (EGVB), enabling early identification of high-risk individuals.MethodsA retrospective study analyzed 296 cirrhotic patients with EGVB who received emergency endoscopic therapy from January 2020 to February 2025. Patients were divided into success (n = 273) and failure (n = 23, defined as bleeding recurrence within 5 days) groups. LASSO regression optimized variable selection, and multivariate logistic regression identified independent predictors to create a nomogram. Internal validation used Bootstrap resampling (500 iterations). Model performance was assessed using ROC curves, calibration plots, and decision curve analysis (DCA), and compared with CTP (Child-Turcotte-Pugh), MELD (Model for End-Stage Liver Disease), and Rockall scores.ResultsThe cumulative incidence of endoscopic failure was observed to be 7.8%. Independent predictors identified included a shock index (SI) > 1.2 (OR = 5.447), the presence of a red color (RC) sign (OR = 10.005), active bleeding observed during endoscopy (OR = 5.962), and the CTP (OR = 1.584). The nomogram exhibited superior discriminatory power with an AUC of 0.890 (95% CI: 0.820–0.960), outperforming the CTP (AUC = 0.771, 95% CI: 0.656–0.886; P < 0.001), MELD (AUC = 0.733, 95% CI: 0.616–0.849; P < 0.001), and Rockall (AUC = 0.656, 95% CI: 0.545–0.768; P < 0.001). Calibration was satisfactory as indicated by the Hosmer–Lemeshow test (χ2 = 10.021, P = 0.263). DCA demonstrated a clinical net benefit across a broad range of thresholds.ConclusionA validated nomogram that integrates the SI, RC sign, active bleeding, and CTP provides an effective prediction of the risk of endoscopic hemostasis failure in patients with cirrhotic EGVB, thereby facilitating timely intervention.